Allopurinol causing generalized exfoliative dermatitis: a case report - Htay, Mila Nu Nu; Myint, Wai Wai; Lwin, Htay; Htay, Win (International Journal of Basic & Clinical Pharmacology, 2017)
Erythroderma is a scaly, erythematous dermatitis of the skin, which occurs in drug allergy, malignancy and underlying skin disorders. The diagnosis is challenging because the extent of skin involvement does not always correlate with the extent of internal organ involvement. Therefore, early recognition of symptoms is vital to minimize morbidity and mortality. Case report: A 52 years old man had asymptomatic hyperuricemia and prescribed allopurinol 300mg, daily. One month later, the rashes started to appear on his trunk and then progressed to the face and upper limbs. Then it continued to spread to the lower extremities. Management involves prompt cessation of the culprit drug, administration of corticosteroids and supportive treatment. It is Concluded that Allopurinol is commonly used in clinical practice for the treatment of symptomatic hyperuricemia and gout. It has been associated with erythroderma especially when used indiscriminately.